UJI AKTIVITAS ANTIBAKTERI SEDIAAN FACE TONER EKSTRAK ETANOL 70% DAUN SALAM (Syzygium polyanthum) TERHADAP BAKTERIStaphylococcus aureus - Sony Hartono; Wahyu Purwanjani; Maulita Saraswati (Universitas An Nuur, 2024)
Background: Salam leaves contain several chemical compounds including alkaloids, flavonoids, saponins, triterpenoids and tannins which are active compounds that are effective as drugs that can cure infectious diseases caused by bacteria. Purpose: The purpose of this study was to determine the antibacterial activity of bay leaf extract face toner preparations against Staphylococcus aureus bacteria. Method: Bay leaves are extracted with 70% ethanol by maceration. The ethanol extract of bay leaves is formulated into a facial toner preparation and then tested for antibacterial activity using the disc diffusion method or the Kirby Bauer method. Results: The results of the research show that the face toner preparation with 70% ethanol extract of salam (Syzygium polyanthum) contains alkaloid compounds, flavonoids, saponins, triterpenoids and tannins. Ethanol extract of salam leaf has antibacterial activity against Staphylococcus aureus with the inhibition zone diameter of F1 of 10.28 mm, F2 of 11.24 mm, and F3 of 12.24 mm. Conclusion: Facial toner preparation of bay leaf extract (Syzygium polyanthum) provides the strongest antibacterial activity in F3 against the growth of Staphylococcus aureus bacteria with an inhibitory zone diameter of 12.24 mm